THE INTEGRATED APPROACH TO THE STUDY OF THE SOCIAL AND ECONOMIC CONSEQUENCES OF UNEMPLOYMENT IN REPUBLIC OF POLAND - Korchak, L. (Continuing Professional Education: Theory and Practice, 2019)
The views of the science from the different fields of knowledge (economy, sociology, psychology, law, political science) on the problem of the unemployment are analyzed in the article; the main reasons of the unemployment among which are the factors that are connected with the state of health, the social and personality factors are defined; the forms of the struggle against the unemployment and the forms of the social assistance to unemployment are characterized. In terms of the social support, the main form of the help the unemployed people is the social work that gives the chance to avoid the marginalization; corrects the functioning of the unemployed people‘s families and also names the ways of the getting out of the crisis situations. Meanwhile the social worker should act as the consultant, inspirator and catalyst for the unemployed people. The financial and material helps are consider to be only as the addition to the social work, as the motivational factors for the unemployed people that stimulate them to active interaction in the solving of their own problems and getting the new job.